2012
DOI: 10.1098/rspb.2012.1659
|View full text |Cite
|
Sign up to set email alerts
|

The yield of experimental yeast populations declines during selection

Abstract: The trade-off between growth rate and yield can limit population productivity. Here we tested for this lifehistory trade-off in replicate haploid and diploid populations of Saccharomyces cerevisiae propagated in glucose-limited medium in batch cultures for 5000 generations. The yield of single clones isolated from the haploid lineages, measured as both optical and population density at the end of a growth cycle, declined during selection and was negatively correlated with growth rate. Initially, diploid popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Correlations between growth rate and yield have long been the focus of r/K selection studies; some of these experiments have indeed found tradeoffs between growth rate and yield [15][16][17]44], but others have found no tradeoff, or even a positive correlation [5-7, 12, 13]. Measurements of lag times have also found mixed results [6,11,41,42,46].…”
Section: B Pleiotropy and Correlations Between Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations between growth rate and yield have long been the focus of r/K selection studies; some of these experiments have indeed found tradeoffs between growth rate and yield [15][16][17]44], but others have found no tradeoff, or even a positive correlation [5-7, 12, 13]. Measurements of lag times have also found mixed results [6,11,41,42,46].…”
Section: B Pleiotropy and Correlations Between Traitsmentioning
confidence: 99%
“…2B,C), as commonly considered in r/K selection studies [5,7,[12][13][14][15][16][17]. If the mutant has a longer lag time, then having a higher yield will be advantageous since the greater resource efficiency gives the mutant more time to grow exponentially to make up for its late start (Fig.…”
Section: Selection Is Frequency-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…A lthough the existence of tradeoffs in evolution seems to be undisputable, experimental evidence obtained under controlled conditions is scarce. Several examples failed to show tradeoffs (1)(2)(3)(4), whereas others could find them (5,6) or found general but not universal tradeoffs (7,8). A tradeoff between growth rate and growth yield in microbes (9-11) has direct implications for experiments carried out in liquid cultures.…”
mentioning
confidence: 99%
“…This is especially of importance during prolonged cultivations such as laboratory evolution experiments. In suspension, fast-growing variants outcompete slower growing ones at the cost of biomass yield (5). The yield versus rate optimization is governed by a dilemma where fast growth is advantageous from the perspective of an individual cell, whereas slow growth, and therefore high yield, is advantageous from the perspective of a population.…”
mentioning
confidence: 99%